El uso de drogas en acuacultura: ¿te dispones a aplicar una droga y/o químico en tu sistema de cultivo? - Montoya, Nelson (2002)
El uso de drogas en acuacultura: ¿te dispones a aplicar una droga y/o químico en tu sistema de cultivo?.